Frontline Ukraine : crisis in the borderlands - Sakwa, Richard (I. B. Tauris, 2015)
The unfolding crisis in Ukraine has brought the world to the brink of a new Cold War. As Russia and Ukraine tussle for Crimea and the eastern regions, relations between Putin and the West have reached an all-time low. How did we get here? Richard Sakwa here unpicks the context of conflicted Ukrainian identity and of Russo-Ukrainian relations and traces the path to the recent disturbances through the events which have forced Ukraine, a country internally divided between East and West, to choose between closer union with Europe or its historic ties with Russia. In providing the first full account of the ongoing crisis, Sakwa analyses the origins and significance of the Euromaiden Protests, examines the controversial Russian military intervention and annexation of Crimea, reveals the extent of the catastrophe of the MH17 disaster and looks at possible ways forward following the October 2014 parliamentary elections. In doing so, he explains the origins, developments and global significance of the internal and external battle for Ukraine. With all eyes focused on the region, Sakwa unravels the myths and misunderstandings of the situation, providing an essential and highly readable account of the struggle for Europe's contested borderlands. -- from dust jacket.